DE-based robust controller design for helicopter cruise control - Mahmud, Iwan; Akmeliawati, Rini; Budiyono, Agus (UNSYS digital, 2014)
This paper presents a robust state feedback controller tuning via constrained optimization using DE (differential evolution). The controller gain is optimized based on the plant model such that the closed-loop system achieves maximum stability radius. The desired control performance is specified by assigning closed-loop poles region which is handled as a constraint in the DE-based optimization. The proposed controller design technique is applied to a longitudinal cruise control of a small-scale helicopter. The control of small-scale helicopter is a MIMO problem which increases the complexity of the controller design task. The proposed controller design attempts to simplify this complicated task where the automated design is employed via DE-based modern optimization. The effectiveness of the proposed controller design technique is presented by comparing its performance with that of conventional LQR-based controllers in computer simulation.